ANALISIS KINERJA PEGAWAI DI PUSKESMAS KEMPAS JAYA KABUPATEN INDRAGIRI HILIR - jurnalmap map; Muhammad Ali; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
The purpose of this study was to determine the analysis of employee performance at the Kempas Jaya Health Center in Indragiri Hilir Regency. The research method used in this study is to use a quantitative approach that is to provide a clear picture of the problem under study, explain the data systematically at the Puskesmas Kempas Jaya Regency of Indragiri Hilir by using questionnaire data collection, observation, study documentation about matters relating to research this. From this study it can be concluded that the performance of employees at the Kempas Jaya Health Center in Indragiri Hilir Regency is already good, but factors that affect employee performance should be improved in terms of work ability, work motivation and job opportunities / opportunities.